Sex-specific socioeconomic risk factors for spontaneous subarachnoid hemorrhage—a case–control study during the 5 years before ictus - Ronne-Engström, Elisabeth; Friberg, Emilie (Frontiers in Public Health, 2024)
Background There is a sex difference in the incidence of spontaneous subarachnoid hemorrhage (SAH) and a majority of SAH cases are women. This has been studied from a medical perspective but the reasons why female sex dominates are still unclear. Non-medical factors, such as the patient's socioeconomic situation, can differ between women and men with health implications. The aim of the study was to try to identify socioeconomic profiles for both sexes, that could be vulnerable to develop SAH. This information could possibly be used for active preventive health work.Methods The material was a 7-year consecutive cohort of 890 patients with SAH treated at Uppsala university hospital, and a sex and age matched 5:1 control group from Statistics Sweden. Information included demography, income that was studied through "earnings" (EA) defined as the sum of the income and other economic compensations related to work, and "disposable income" (DI) which is the net amount that the individual can use. Pension and sickness related absence from work was measured by early pension (EP), old age pension (OAP), sickness absence (SA) and disability pension (DP). Univariate and multivariate analyses methods were used.Results Among women, a socioeconomic risk profile for SAH included lower education, being unemployed, registered as living as a single, living in a sparsely populated municipality and increased age. For men, the risk profile included living in a sparsely populated municipality and changing civil status. Both women and men with SAH had lower EA and DI compared to the controls. Significantly more women with SAH had DP, compared to controls.Conclusion Living in a sparsely populated area was associated with increased risk for SAH for both sexes. Women with a SAH were more vulnerable economically, whereas men had another type of vulnerability related to change of civil status. We suggest that health-care organizations could use the information in identifying individuals at risk and actively work with preventive measures according to stroke guidelines in both these two groups.